Beyond the whole-mount phenotype: high-resolution imaging in fluorescence-based applications on zebrafish - Oralová, Veronika; Rosa, Joana T; Soenens, Mieke; Bek, Jan Willem; Willaert, Andy; Witten, Paul Eckhard; Huysseune, Ann (Biology open, 2019)
Zebrafish is now widely used in biomedical research as a model for human diseases, but the relevance of the model depends on a rigorous analysis of the phenotypes obtained. Many zebrafish disease models, experimental techniques and manipulations take advantage of fluorescent reporter molecules. However, phenotypic analysis often does not go beyond establishing overall distribution patterns of the fluorophore in whole-mount embryos or using vibratome or paraffin sections with poor preservation of tissue architecture and limited resolution. Obtaining high-resolution data of fluorescent signals at the cellular level from internal structures mostly depends on the availability of expensive imaging technology. Here, we propose a new and easily applicable protocol for embedding and sectioning of zebrafish embryos using in-house prepared glycol methacrylate (GMA) plastic that is suited for preservation of fluorescent signals (including photoactivatable fluorophores) without the need for antibodies. Four main approaches are described, all involving imaging fluorescent signals on semithin (3 µm or less) sections. These include sectioning transgenic animals, whole-mount immunostained embryos, cell tracking, as well as on-section enzyme histochemistry.
Keywords: GFP; Fluorophores; Cell tracking; TRAP; Zebrafish; GMA; Immunofluorescence